Servo control of drive-trains incorporating magnetic couplings - Liao, Xiaowen; Bingham, Chris; Zolotas, Argyrios; Zhang, Qinghua; Smith, Tim (IEEE, 2022)
The paper presents a high performance and low-cost design methodology for the servo control of magnetic drive-trains (MDTs) operating in direct drive mode. For the first time, this paper considers using sensitivity peaks to analyse the robustness and stability of MDT control systems. Initially, through analysis of a dynamic model, the key spring characteristic parameters with respect to operating points, are developed. It is also shown that a wider dynamic performance envelope can be achieved by linearizing the MDT model at around 60 % -80 % of the maximum coupling torque, as opposed to traditional linearization under zero torque conditions. Subsequently, the paper exploits the spring characteristics for a design methodology based on the H∞ mixed sensitivity approach to determine suitable control parameters. Following this, the maximum exogenous load-torque disturbance and speed reference can be determined that will not induce pole-slipping. Finally, preferential position reference profiles and optimal gains for position controllers are given to prevent demand-induced speed oscillations. The proposed methodologies are validated through simulation and experimental studies.
Keywords: Magnetic coupling; linearization; spring dynamics; two-degree-of-freedom PI; H mixed sensitivity; servo control